2013
DOI: 10.1016/j.jcrs.2012.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Decreased postoperative endophthalmitis rate after institution of intracameral antibiotics in a Northern California eye department

Abstract: The adoption of intracameral antibiotic injection coincided with a decline in the rate of postoperative endophthalmitis, and a low infection rate was observed with intracameral injection alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 24 publications
3
98
1
7
Order By: Relevance
“…19,20 Although a 10-year comparative study in Spain corroborated the ESCRS study findings 21 and this has become a standard of care in the European countries, it is far from fully recognized in other countries. Outside Europe, only 2 studies (USA 22 and South Africa 23 ) have reported significantly lower rates of postoperative endophthalmitis with the use of prophylactic intracameral cefuroxime. At our clinic, all surgeons follow a uniform preoperative and postoperative protocol for cataract surgery, and surgery is performed using topical or peribulbar anesthesia.…”
mentioning
confidence: 99%
“…19,20 Although a 10-year comparative study in Spain corroborated the ESCRS study findings 21 and this has become a standard of care in the European countries, it is far from fully recognized in other countries. Outside Europe, only 2 studies (USA 22 and South Africa 23 ) have reported significantly lower rates of postoperative endophthalmitis with the use of prophylactic intracameral cefuroxime. At our clinic, all surgeons follow a uniform preoperative and postoperative protocol for cataract surgery, and surgery is performed using topical or peribulbar anesthesia.…”
mentioning
confidence: 99%
“…The patients who received intracameral antibiotics were found to have a 13 fold lower rate of infection as compared to the patients who did not receive intracameral antibiotics. 48 Yu-Wai-Man et al carried out a retrospective study of more than 36000 patients who underwent cataract surgery to compare the rates of endophthalmitis between subconjunctival (50mg in 0.5ml) versus intracameral (1mg in 0.1ml) cefuroxime prophylaxis. The incidence of endophthalmitis was lower in patients who had received intracameral cefuroxime (0.046%) than in those who had received subconjunctival cefuroxime (0.139%), and this difference was statistically significant (p=0.0068).…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…Outside Europe, only 2 studies (USA and South Africa) have reported significantly lower rates of postoperative endophthalmitis with the use of prophylactic intracameral cefuroxime. 48,56 A prospective study of more than 15000 patients undergoing cataract surgery was carried out in a tertiary eye care centre in India. The aim of the study was to find out if the addition of intracameral cefuroxime to the existing endophthalmitis prophylaxis protocol resulted in any additional benefit.…”
Section: Intracameral Antibioticsmentioning
confidence: 99%
“…17,18 Since the routine introduction of intracameral injection of cefuroxime 6 years ago, the rate of endophthalmis has been significantly reduced. [19][20][21][22][23][24][25] Furthermore, a commercially available formulation of cefuroxime (Aprokam ® ) approved for intracameral prophylaxis was introduced to the European market in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25]38 The ESCRS has been recommending to administer cefuroxime in the anterior chamber in all cases of cataract surgery since 2007. [17][18][19] However, the additional protective role of cefuroxime over the standardized protocols is still a matter of debate.…”
mentioning
confidence: 99%